2017
DOI: 10.1155/2017/8917957
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Shrinkage Reducing Agent and Expansive Additive on Mortar Properties

Abstract: This research is to study the effect of mortar mixed with shrinkage reducing agent (polyoxyalkylene alkyl ether type), expansive additive (CaO type), and fly ash (hereinafter "SRA," "EX," and "FA," resp.). Moreover, steam curing was studied to improve the properties of mortar. The plastic shrinkage test was conducted by using the strain gauge embedded at 0.5 cm from the surface according to the ASTM C1579-06 standard within early age followed by the total shrinkage test and compressive strength test. The test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…e data is comparable to the previous studies. For example, research by Xie et al [23] showed that, with 2% SRA addition, 65.6% reduction in autogenous shrinkage can be achieved compared to the reference plain UHPC at 7 d. Similarly, Su et al [25] reported an up to 95% reduction in autogenous shrinkage with 2% SRA dosage at 7 d.…”
Section: Autogenous Shrinkage Of Uhpcmentioning
confidence: 99%
“…e data is comparable to the previous studies. For example, research by Xie et al [23] showed that, with 2% SRA addition, 65.6% reduction in autogenous shrinkage can be achieved compared to the reference plain UHPC at 7 d. Similarly, Su et al [25] reported an up to 95% reduction in autogenous shrinkage with 2% SRA dosage at 7 d.…”
Section: Autogenous Shrinkage Of Uhpcmentioning
confidence: 99%
“…Thus, the steam curing which helps improve the compressive strength has been used in this experiment. [6,7] Studies on the shrinkage and expansion property from using the 3 materials and its impacts are rare. Hence, further thorough studies concerning the expansion property from the use of local materials are considerably necessary.…”
Section: Introductionmentioning
confidence: 99%